Effect of peri-operative chemotherapy regimen on survival in the treatment of locally advanced oesophago-gastric adenocarcinoma – A comparison of the FLOT and 'MAGIC' regimens. (March 2022) - Moore, Jonathan L.; Kumar, Sacheen; Santaolalla, Aida; Patel, Pranav H.; Kapiris, Matthaios; Van Hemelrijck, Mieke; Maisey, Nick; Hill, Mark; Lagergren, Jesper; Gossage, James A.; Kelly, Mark; Chaudry, Asif; et al.
Abstract: Background: Peri-operative chemotherapy improves survival in patients with locally advanced oesophago-gastric adenocarcinoma. Two regimens with proven survival benefits are epirubicin, cisplatin plus capecitabine or fluorouracil (Medical Research Council Adjuvant Gastric Infusional Chemotherapy, MAGIC) and fluorouracil plus leucovorin, oxaliplatin, and docetaxel (FLOT). This study aimed to compare the effect of these regimens on survival (primary aim) and pathological response, surgical complications, adverse events and chemotherapy completion rates. Methods: Cohort study including 946 patients treated with FLOT (n = 257) or MAGIC (n = 689) who underwent surgical resection for oesophageal (n = 743) or gastric (n = 203) adenocarcinoma between 2002 and 2021 at St Thomas' Hospital or The Royal Marsden Hospital, London, UK. Survival analysis was performed using multivariable Cox regression, providing hazard ratios (HRs) with 95% confidence intervals (CIs) adjusted for age, sex, clinical T-stage, clinical N-stage, tumour grade and presence of signet ring cells. Results: Patients treated with FLOT had better overall survival (HR = 0.69, 95% CI 0.50–0.94) and disease-free survival (HR = 0.75, 95% CI 0.58–0.98) than MAGIC. Patients treated with FLOT were more likely to have a complete pathological response (9.5% FLOT versus 5.5% MAGIC, p = 0.027) and were less likely to have a positive resection margin (19.1% FLOT versus 32.2% MAGIC, p < 0.001). The stratified analysis revealed similar results for oesophageal and gastric tumours. Rates of surgical complications, chemotherapy-associated adverse events and completion were similarly distributed between treatment groups. Conclusions: Patients with oesophageal or gastric adenocarcinoma treated with peri-operative FLOT had better survival and pathological response than those treated with peri-operative MAGIC. Rates of surgical complications, adverse events and chemotherapy completion were comparable. Highlights: Better survival in patients treated with fluorouracil plus leucovorin, oxaliplatin and docetaxel. Better pathological and radiological response to chemotherapy with FLOT. Higher rates of complete pathological response in patients treated with FLOT. Patients treated with FLOT were less likely to have a positive resection margin. Comparable rates of surgical complications, adverse events and chemo completion.